Intense antithrombotic therapy is necessary for long-term treatment in patients with symptomatic peripheral artery disease after acute myocardial infarction and primary PCI. (25th November 2020) - Motovska, Z; Hlinomaz, 0; Kala, P; Knot, J; Jarkovsky, J; Hromadka, M; Varvarovsky, I; Dusek, J; Tousek, F; Simek, S; Vodzinska, A; Svoboda, M; et al.
Abstract: Background: Evidence about the benefit of intense dual antiplatelet therapy in patients with peripheral artery disease (PAD) and concomitant coronary artery disease is controversial. Purpose: To analyze the impact of symptomatic PAD comorbidity on prognosis of patients with acute myocardial infarction (AMI) treated with primary PCI and intense antithrombotic medication. Methods: The study is a post hoc analysis of the multicenter randomized PRAGUE-18 study (prasugrel vs. ticagrelor in primary PCI). During the 12-month follow-up switch to clopidogrel for economic reasons was allowed if approved by treating physician. Out of the whole study population (N=1230), symptomatic PAD was present in 2.9%. Results: No significant difference related to the presence of PAD was observed neither in primary net clinical endpoint (death, reinfarction, urgent target vessel revascularization, stroke, severe bleeding requiring transfusion or prolonged hospitalization) at 7th day nor in combined ischemic endpoint (CV death, MI, stroke) within 30-days. At one year, the risk of death was higher in patients with concomitant PAD (Figure). But, the risk of death was significantly increased only in patients who switched to clopidogrel [6.37 (2.16–18.84), p=0.001]. The difference in risk of death related to the presence of symptomatic PAD didn't reach significance [3.02 (0.72–12.61), p=0.13] in patients who continued on ticagrelor/prasugrel. The landmark analysis from the day 30 up until the end of the study showed that the risks of CV death and all-cause death were significantly higher in PAD patients [6.13 (1.37–27, 38), p=0.018 and 9.66 (3.61–25.87), p<0, 001 respectively]. The significant impact of PAD on the long-term outcome, however, was also present only in patients, who switched to clopidogrel. No difference was found in the occurrence of bleeding events between patients with (8.3%) and without (11.1%) PAD throughout the whole study period (p=0.66). Conclusion: Presence of PAD significantly impacts prognosis of patients after AMI; especially in those who de-escalate the antiplatelet medication. Long-term intense antithrombotic medication is necessary for patients after AMI with concomitant symptomatic PAD. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): The Charles University Cardiovascular Research Program